Experiments on the structure of baroclinic waves and zonal jets in an internally heated, rotating, cylinder of fluid - Bastin, M; Read, P (1998)
In this paper we report a laboratory investigation of the motion within a rotating cylinder of fluid subject to internal heating and to cooling at the outer cylindrical sidewall. The internal heating is supplied by ohmic dissipation as an electric current passes between the outer sidewall and an axial wire. The experiments focus on the formation of eddy features and the associated zonal jets. To identify how the flow regimes generated in this continuously forced system are modified by the presence of a radial depth gradient, experiments have been performed with both horizontal (f-plane) and oppositely sloping boundaries. Endwall configurations which cause the fluid depth (D) to increase with radius (∂D/∂>0) and to decrease with radius (∂D/∂r<0) have been studied, as the former is applicable to the terrestrial atmosphere and oceans, while the latter may be relevant to deep atmospheres such as those of the giant planets and even planetary interiors. Stable, coherent, regular eddy features are observed over a wide range of rotation rates (Ω) in both horizontal and oppositely sloping endwall experiments. In the f-plane experiments regular modes with azimuthal wavenumbers m = 1 and m = 2 are observed. The regular wave regime of the ∂D/∂r>0 endwall experiments consists of modes with azimuthal wavenumbers m = 1 to 5. Only the mode m = 1 is seen in the regular wave regime of the ∂D/∂r<0 endwall experiments. The regular eddy structures produced in the ∂D/∂r>0 (∂D/∂r<0) endwall experiments are seen to be "vertically trapped" close to the bottom (top) boundary, whilst the amplitude of the f-plane modes is found not to vary substantially with depth. Further effects of the radial depth gradient are the observed reduction in the lateral scale of the eddy features in the ∂D/∂r>0 endwall experiments, which leads to the formation of between two and three independent trains of eddies within the lateral domain at sufficiently high values of Ω. Within the non-axisymmetric flow regimes of all three endwall configurations the number of zonal jets observed in the lateral domain of the experiment is larger than expected from the form of the background thermal forcing. The radial scale of the multiple zonal jets seen in the oppositely sloping boundary experiments is, however, much larger than a barotropic Rhines scale L β, suggesting that L β cannot be used to predict the radial wavenumber of the zonal mean flow in this continuously forced system. © 1998 American Institute of Physics.